PERANTAU DESA DELUK KECAMATAN BANTAN KABUPATEN BENGKALIS - Ardila, Nur; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the village of Deluk sub-district of Bengkalis Regency Bantan. The purpose of this research is to know the towing and factors driving factor nomads in the village of Deluk sub-district of Bengkalis Regency bantan. The topic of this research focus is characteristic of nomads in the village of Deluk sub-district of Bengkalis Regency bantan. The sample in this study amounts to 50 people. The author uses quantitative methods and use techniques of retrieval of quota Sampling. Data instruments are observation, question form and documentation. From the research that is done, the authors find that towing (pull factors) one that is a lot of job opportunities, where researchers found that 39 people (78%), or The Wanderer gained a great opportunity to get a permanent job when going about as well as can earn higher incomes where researchers found namely the 26 people or (52%) from activities abroad gives the changes in the level of earnings. As for the driving factor (push factors) of poverty to become one of the factors which the Research found that nearly all respondents approve if they wander due must meet the economic needs of the family with a high number of  respondents who replied concur that is 28 people or (56%) and who answered strongly agree totalling 22 or (44%). The impact of social economy against the nomads wander is the occurrence of a change of social status as a result of increased earned income.    Keywords: Social Mobility, Nomads